Health matters: a statistical approach to understand childhood illnesses in the North-East States of India, 2019-2021 - Mukesh Ranjan; Lalrotlinga; Ashutosh Singh; Brajesh; Vanlalhriatsaka (BMC, 2024)
Abstract The present study explores the prevalence and socio-economic demographic factors affecting childhood illnesses. Diarrhoea, fever and ARI among under-five children in the North -East states of India using NFHS-5 data Kids file. Results showed that diarrhoea, ARI, and fever among the northeastern states were highest in Meghalaya.For diarrhoea Sikkim has the highest prevalence for children within 6 months while Meghalaya has the highest prevalence in the age groups 6- 12 months and 1- 2 years old children and Arunachal Pradesh has the highest rate in the age group 2- 5 years old children. Meghalaya stands out with the highest prevalence of fever and ARI in all age groups. Compared to Sikkim, the state of Meghalaya had more diarrhoea, ARI and fever, and it was statistically highly significant. However, Tripura and Assam had significantly higher odds of having fever and ARI than Sikkim. There is an association between diarrhoea, fever, and ARI and factors such as the age of the child and caregiver, the wealth status of the household, the quality of sanitation facilities, methods of stool disposal, and the caregiver's educational level.